STEFAN ZAHORSKI (1933-1999) - Obituary - Ziabicki, A. (Archives of Mechanics, 1999)
On 28th of August, 1999 passed away Professor Stefan Zahorski, PhD, DSci., director of Polymer Physics Group, Institute of Fundamental Technological Research (IFTR), Polish Academy of Sciences in Warsaw, active member of the Editorial Committee of Archives of Mechanics.